Is Cancer Inevitable? - Weeraratna, Ashani T., 1970- (Book collections on Project MUSE., 2021)
"The author, a researcher in oncology, studies the cellular mechanisms of carcinogenesis. In this book written for a popular audience, the author takes a step back from the details of cells to look at the broader issue of how aging affects cancer"--